The girl that can't get a girlfriend - Hiranishi, Mieri (VIZ Originals, 2023)
"Mieri is an awkward, nerdy college student with no dating experience, and her previous crushes on fellow butch women have all ended in disaster. That all changes when she meets Ash and has her feelings returned for the first time. But when first love turns to first heartbreak, Mieri will do everything possible to win Ash back."--